Mengukur Determinasi Variabel Makroekonomi dan Indeks Saham Syariah Indonesia: Analisis Error Correction Model - Ardana, Yudhistira; Dian Sugiarti (Universitas Muhammadiyah Surabaya, 2024)
In the Indonesian economy, the capital market is very important because it functions as an intermediary between parties who need funds and parties who have excess funds. This institution exists not only as a source of funding but also as a means. This research aims to analyze the influence of macroeconomic variables proxied by inflation, money supply, world gold prices, and world oil prices on the Indonesian Sharia Stock Index using the Error Correction Model. The research results show that both short-term and long-term macroeconomic variables simultaneously influence the Indonesian Sharia Stock Index. Meanwhile, partially, in the short term and long term, the money supply variable has a significant negative effect. The world gold price variable, both short-term and long-term, has a positive and insignificant effect. The world oil price variable, both short- and long-term, has a significant positive effect. The short-term inflation variable has an insignificant negative effect, and the long-term variable has a significant positive effect.